2017
DOI: 10.1187/cbe.16-11-0333
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Novice and Expert Conceptions of Genetically Modified Organisms

Abstract: This work extends previous studies exploring how undergraduate science students apply their classroom biology knowledge to everyday phenomena—in this case, genetically modified organisms (GMOs). Also described are how intuitive ways of thinking might underlie misconceptions that interfere with students applying their biology knowledge to GMOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…For example, studies have found that many ABM who have taken course work in evolution and genetics do not use their knowledge of natural selection to accurately describe antibiotic resistance ( Richard et al. , 2017 ) or their molecular biology knowledge to describe a GMO ( Potter et al. , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have found that many ABM who have taken course work in evolution and genetics do not use their knowledge of natural selection to accurately describe antibiotic resistance ( Richard et al. , 2017 ) or their molecular biology knowledge to describe a GMO ( Potter et al. , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…While many college undergraduates take a biology course, either as a stand-alone course or as part of a biology major, college biology students often have difficulty relating their biology knowledge to real-world issues. This disconnect is apparent in topics as disparate as genetically modified organisms (GMOs) and antibiotic resistance ( Potter et al. , 2017 ; Richard et al.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that many of the students who initially did not use central dogma-related ideas did possess the basic knowledge about the central dogma and were able to apply it once that knowledge was brought to mind. This finding is useful for vaccine education given that other research has found that the efficacy of cues for prompting students to apply their biology knowledge may differ by topic ( 2 , 14 ). However, it is also important to note that not all the ideas produced in the cued condition were scientifically accurate.…”
Section: Discussionmentioning
confidence: 73%
“…It is critical for biology educators to prepare students to apply their biology knowledge to understand societally relevant biology topics ( 1 ). However, it can be difficult for students to do this, especially without a cue that signals to students that their classroom knowledge may be relevant ( 2 , 3 ). The coronavirus disease 2019 (COVID-19) pandemic highlighted the importance of vaccination for protecting against infectious disease ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies of experts and novices in different subject areas have been central to understanding domain-general and domain-specific features of problem representation and problem-solving performance for nearly a century (reviewed in Novick and Bassok, 2012). Novice-expert comparisons have seen comparatively little use in BER, although some notable exceptions include studies in genetics (Smith, 1983), evolution (Nehm & Ridgway, 2011), and genetically-modified organisms (Potter et al 2017). These studies offer a range of insights into how novices and experts conceptualize problems, plan solutions, and utilize concepts and frameworks in problemsolving tasks.…”
Section: What Cognitive Framework Could Guide Ber?mentioning
confidence: 99%